Settler colonial archives: some Canadian contexts. (3rd July 2019) - Griffith, Jane
ABSTRACT: Archives became a central part of Canada's Truth and Reconciliation Commission (TRC) into Indian residential schools over its 7-year course. The Commission's mandate included the creation of a National Centre for Truth and Reconciliation: a permanent archive of residential school history as well as a place to house records of the Commission's work. The TRC's final Calls to Action also recommended reform to archival institutions in Canada. This paper focuses on the central role that archives played during the TRC and what these realities might offer for considering methodologies and settler colonial archives more generally. It begins with a detailed description of the TRC's archival layers and then zooms out to larger considerations of state archives and settler colonialism. The paper then considers the settler colonial language and metaphors often used in archival research and then offers several 'archive stories' or field notes, from the author's larger research. It concludes with new directions in understanding archives.